BEING AT HOME IN SOLITARY QUARANTINE. PHENOMENOLOGICAL ANALYTICS AND EXISTENTIAL MEDITATIONS - Nader EL-BIZRI (Studia Universitatis Babeș-Bolyai. Philosophia)
This ontological investigation is mediated via multifaceted phenomenological analytics and existential mediations over the architectural mode of being at home in solitary quarantine under communal global lockdowns. The present line of inquiry is undertaken by way of probing the attuned metamorphoses in solitude of the lived experiencing of the intertwined phenomena of space-time, embodiment-in-the-flesh versus being-with-others via cybernetic and telecommunication technologies, dwelling amidst things and paraphernalia, and the underlying affectivities of the mode of being-toward-death.